Online removal of sodium dodecyl sulfate via weak cation exchange in liquid chromatography-mass spectrometry based proteomics - Serra, Aida (2020)
Biological research often requires the use of sodium dodecyl sulfate (SDS) to solubilize protein samples; however, this detergent is not compatible with direct mass spectrometry (MS) analysis. Here, we report an online high-throughput proteomics method that permits standard in-solution digestion of SDS-containing samples followed by direct liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS) analysis using weak cation-exchange chromatography (WCX). This approach, called the online removal of sodium dodecyl sulfate (Online reSDS), exploits the properties of WCX in a highly organic and mildly acidic medium to retain positively charged peptides by both hydrophilic interaction and electrostatic attraction while simultaneously repelling negative SDS molecules. This method was optimized to successfully analyze complex samples that contain up to 1% of SDS. Furthermore, online reSDS improves the identification of peptides with post-translational modifications (PTMs), such as deamidation and phosphorylation, without preliminary enrichment. In conclusion, we show that reSDS can facilitate research in proteomics by allowing the use of SDS in a wide range of LC-MS/MS applications with simplified sample-processing procedures.